2016
DOI: 10.17795/semj41542
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Tuberculosis in HIV/AIDS Patients Referred to Behavioral Diseases Consultation Center: A Registry-Based Study in Abadan, Southwest of Iran

Abstract: Background: In the world, it is estimated that 36.9 million people are living with HIV (PLHIV). Tuberculosis (TB) remains as the leading cause of death among PLHIV. This study aimed to determine the predictors of TB among HIV positive patients. Methods: This cross-sectional study was based on the data from 366 patients with HIV/AIDS acquired from 2010 to 2013 in Abadan and Khorramshahr cities, southwest of Iran. Demographic and clinical data were obtained from patients' medical records in Abadan and Khorramsha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Nevertheless, in contrast to the study conducted in Gambia [21] alcohol use is not associated with TB infection, this is because of socio-demography, sampling technique difference and sample size. Smoking was not associated with increased TB infection in this study; this is in agreement with previous study conducted in Addis Ababa [22]. However, in other study conducted in West Africa [19], which identi ed smoking as predictors for increased TB infection among HIV infected adults, this difference was probably due to sample size difference, social desirability bias where smokers deprived of their smoking status in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, in contrast to the study conducted in Gambia [21] alcohol use is not associated with TB infection, this is because of socio-demography, sampling technique difference and sample size. Smoking was not associated with increased TB infection in this study; this is in agreement with previous study conducted in Addis Ababa [22]. However, in other study conducted in West Africa [19], which identi ed smoking as predictors for increased TB infection among HIV infected adults, this difference was probably due to sample size difference, social desirability bias where smokers deprived of their smoking status in this study.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, malnutrition can aggravate the immune de ciency and increase the risk of active TB. Building on the existing knowledge this study also found out that low body mass index increased the likelihood of tuberculosis infection [22,27]. [34].…”
Section: Discussionmentioning
confidence: 97%
“…Tuberculosis (TB) is the most frequently diagnosed opportunistic infection among people living with human immunodeficiency virus (PLHIV). It remains one of the world's leading causes of ill health and death among PLHIV [1][2][3][4][5]. Due to the immunological impairment associated to HIV infection, PLHIV are at higher risk of developing TB [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, malnutrition can aggravate the immune deficiency and increase the risk of active TB. Building on the existing knowledge this study also found out that low body mass index increased the likelihood of tuberculosis infection [22,27]. [34].…”
Section: Discussionmentioning
confidence: 97%